“Student preference towards the utilization of Edmodo as a learning platform to develop responsible learning environments" study - Asih Nur Halimah; Hilmy Abdullah (International Transactions on Education Technology (ITEE), 2022)
Teachers can simply establish and administer online learning communities using Edmodo, and students may connect and collaborate with their peers and teachers whenever they want, from any location. A safe and cost-free educational learning network, Edmodo. To promote participation and responsible learning, this study sought to ascertain how much students preferred to utilize the academic social networking site Edmodo. The goal of this essay is to determine whether using Edmodo as a teaching tool is appropriate that more teachers should employ to support a student-centered, technologically-based learning environment where students participate and put their ideas about responsible learning into practice. The study was carried out in a private institution in Banjarharjo, Central Java. Only 320 of the 280 degree-seeking participants were actually used in the analysis. This study used a quantitative methodology,and a survey with research-designed questions was utilized to collectresponds on a Likert scale of 1 to 5, with 1 being strongly agree and 5 being strongly disagree. To encourage students' decision to utilize Edmodo for teaching and learning, the survey question was developed using the RASE (Resources, Activity, Promote, and Evaluation) method.. The study's findings demonstrate that using specific Edmodo features increases student engagement and promotes responsible learning. The analysis's conclusion confirms that the students prefer Edmodo mostly for its resources. assistance and communication tools including forums, chat rooms, and online activities are also available. Students love working on online classes because of Edmodo's great and user-friendly social learning platform. The findings of this study might prompt educators to reconsider how they run their classrooms.